Adapting the Graphic Novel to Improve Speaking Fluency for EFL Learners - Eva Gultom; Adelle Frans; Esperanza Cellay (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
This study examines the viability of the literature in terms of escalating English speaking fluency for EFL learners. The focus of this study applied graphic novels as a particular research object. As part of literature, the graphic novel has become one of the resources allowing learners to access attractive, inspired, conceptual, and artistic encounters for learners. This study used a quantitative method focused on online class observation and survey analysis. The purpose of this study is to show the impact of literature on EFL learners to speak, to outline the potency of graphic novels to escalate their speaking skills, and to boost their fluency.